Experimental and numerical analysis of the seismic performance of concrete block masonry buildings - Velez, Leonardo Avila (2014)
The increase in housing demand and the construction cost of the necessary houses for its satisfaction have motivated the study of economical and efficient solutions aiming at developing new construction methods. A new solution for the construction of residential houses is presented. Dynamic seismic tests by using a shaking table were performed on two masonry buildings. The first experimental model incorporates steel reinforcement according to the Eurocodes, while the second was tested as an unreinforced solution. A numerical model for the unreinforced solution was prepared by using macro-modelling approach. Five non-linear phased dynamic analyses with time integration representing the same seismic amplitude tests implemented during the experimental campaign were made. In terms of experimental results, the quantitative parameters for both models and the crack patterns are presented. Comparisons between the experimental results and those from the numerical simulations are also presented.